Collaborative software and community building - Williams, Jeffrey B. (Kansas State University, 2005)
How does collaborative software help in the formation of a learning community? This study looks at the experiences of students in a first level Computer Science class as they use Manhattan Virtual Classroom (MVC). Although this case study began with the assumption that a learning community would form, it quickly became obvious that student participation in the MVC was a larger issue. The course chosen for this study was CSC-150 - Foundations of Computer Science, as taught in the Spring 2004 semester at a Midwestern university. Two traditional (face-to- face) course sections were given access to Manhattan Virtual Classroom for the purpose of discussions, comments, questions, and virtual office hours. Many students did not take advantage of this collaborative tool. Several reasons are considered, the reluctance of freshmen to participate (Goldberg, 1997; Carlson et al., 1996), professor teaching style, and student perceptions of their own contributions to the class. Several conclusions are drawn from this study how to increase student participation. These include better training in the use of the software, use of smaller groups within the Manhattan Virtual Classroom environment, clearly stated professor expectations, and a general adoption of this technology for other classes.
Keywords: Community; Collaborative software; Secondary Education (0533)